Prospects and limits to social accountability tools towards enhancing service delivery in Bulawayo urban - Matsika, Lillian (Midlands State University, 2015)
Demand-side governance and social accountability approaches have steadily gained prominence as a means of achieving and improving a range of development outcomes (Holland et al, 2011). A good number of local authorities across the world in both the developed and developing counties are investing in social accountability tools such as citizen participation, budget tracking and expenditure monitoring, community score cards and others to ensure that citizens have a voice in the planning and provision of services and also in finding ways in which service provision can and should be improved.